(untitled) (Ozone Therapy Global Journal, 2013)
Despite the current advances in the medical uses of ozone, some aspects of the clinical handling of this gas have not been clarified and studied property. The present work applies a spectrophotometric method for controlling the concentration of the medical ozone generator. In addition we studied the half life time of the ozone inside a syringe located at different positions. As was demonstrated by performing spectrophotometric measurement (240nm) and by mathematical calculations (taking into account working temperature and pressure) is possible to know the concentration of ozone generated by ozone devices for clinical use. This method is useful in case of doubt about the right functioning of the device or if it suspected a loss of calibration. Additionally, it was demonstrate the importance of using O3 in the first 10 min after being generated, because the loses of the10% of the initial dose. Also it was found that the position, in which the syringe is placed, even if advised to have it with the cone up, is not decisive in handling the gas.